Evolutionary features of the transitional complex in Eastern Ciscaucasia regarding the hydrocarbon prospects of the Karpinsky Ridge - T. Suyunbayev (Известия высших учебных заведений: Геология и разведка, 2025)
Background. This article considers the evolutionary features of formation of the transitional complex in Eastern Ciscaucasia regarding the hydrocarbon prospects of the Karpinsky Ridge.Aim. To research specific evolutionary features of the transitional complex in Eastern Ciscaucasia and to carry out its basin analysis to identify the main components of petroleum systems.Materials and methods. Statistical generalization and regimentation of materials borrowed from reference literature, stock sources, field data, and published worksResults. In the research area, three potential hydrocarbon-bearing rocks were identified, associated with the deposits of the Neftekumskaya and Kultaisko-Demyanovskaya sections of the Lower Triassic, the Kizlyarskaya section of the Middle Triassic, as well as deeply buried Carboniferous deposits as a potential shale source rock.Conclusion. An integrated analysis of well data, geochemical studies, and paleogeographic reconstructions served as the basis for forecasting the main elements of petroleum systems.